Chemometric match to evaluate fatty acids degradation of animal and plant fats after heating treatment by principal component research (PCR) - Salleh N.A.M.; Hassan M.S. (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by Scopus